TRADISI MESBES BANGKE DARI BANJAR BURUAN,TAMPAK SIRING, GIANYAR, BALI - Ida Ayu Putu Sari; I Made Yudabakti (UNHI PRESS, 2022)
ABSTRACT Hinduism is one of the majority beliefs held by the people in Bali. Hinduism is a religion that has the oldest age and is the religion that was first recognized by humans. Hinduism originated in India, this religion is a contest between the religions of the Aryans and the Dravidians. The Aryans who came from Asia Tengah succeeded in urging the native Indians of the Dravina. There was an assimilation between the Aryans and the Dravidians which in turn gaverise to a generation called the Hinduism. The word Hindu comes from the word Sindhu which means river. Thisword refers to the Indus river which is a source of water for the life around it. Sources of Hindu teachings are found in the Veda scriptures (consisting of four books), Brahmans (an interpretations of the Veda), and Upanisads (containing the philosophical foundations of the relationship between human and God). Bali has many traditions. Tradition is a form of action that is repeated in the same way. The word